Strength and conditioning practices of Major League Baseball strength and conditioning coaches - Ebben, W. P.; Hintz, M. J.; Simenz, C. J. (The Journal of Strength and Conditioning Research, 2005)
This study describes the results of a survey of the practices of Major League Baseball strength and conditioning (MLB S&C) coaches. The response rate was 70.0% (21 of 30). This survey examines (a) background information, (b) physical testing, (c) flexibility development, (d) speed development, (e) plyometrics, (f) strength/power development, (g) unique aspects, and (h) comments. Results indicate, in part, that coaches assess an average of 3.6 parameters of fitness, with body composition testing being the most commonly assessed parameter. All coaches use a variety of flexibility development strategies. All coaches use speed development strategies, with form running drills being the most common. Twenty of 21 (95.2%) coaches employ plyometric exercises with their athletes. Eighteen of 21 (85.7%) of MLB S&C coaches follow a periodization model (PM). Five of 21 coaches (23.8%) indicated that their athletes use Olympic-style lifts. The squat and its variations and the lunge and its variations were most frequently identified as the first and second most important exercises used to train the athletes. This survey provides detailed information about strength and conditioning practices at the most competitive level of baseball and serves as a review, as well as a source of applied information and new ideas.